KONTEKSTUALISASI SUFISME BAGI MASYARAKAT URBAN - Rubaidi Rubaidi (Jurnal Theologia, 2019)
This paper critically examines the important roles of the presence of Sufism institutions for the urban middle class. Writing taken from research on the Majelis Shalawat Muhammad in Surabaya and Bojonegoro presents constructive thinking as well as the creative practices of the murshid, Gus Kahar and Gus Mustakim. Both managed to "reconcile" between modernity and spirituality. The concept of positive sufism and positive zuhud based on Gus Kahar and Gud Mustakim make a significant contribution as well as a reference for urban middle-class people who are often confused and uncertain in combining Islam and modernity. In accordance with the mission of Islam from the beginning of its birth, Islam (sufism) taught in the Majelis Shalawat Muhammad was felt to liberate its jama’ah from diseases suffered by urban communities such as the reason for being analyzed, disorientated, distorted, and so on